AHIHA Scarves / Ummi Aliah Abdul Kadir ... [et al.] - Abdul Kadir, Ummi Aliah; Hussin, Nor Hasmida; Gani @ Ghani, Norsyahferra Irani; Zaini, Muhammad Hafiz; Wan Idris, Wan Arina (2021)
Product AHIHA Scarves offers high-quality scarves for women of all ages from children to adults. All scarves are made of premium materials and various types of scarves fabrics such as alpaca, cashmere, cotton, jersey, linen, pashmina, satin and silk. The scarves are designated and manufactured to provide comfort and beautiful appearance to the wearer and help them to boost their confidence when going out to meet a lot of people. Customers The target audience for AHIHA Scarves is adults, specifically working women, parents, grandparents, uncles or aunties who wish to give their children, grandchildren or nieces scarves as presents and boyfriend, husband, brother or son who wish to give their girlfriend, wife, sister or mother the opportunity to wear a scarf that is aesthetically pleasing. Company Future Although the scarves manufacturing business is highly competitive, we believe that there is a place for high-quality, attractive and affordable scarves. Our goal is to manufacture and market scarves that will fulfil the needs of the wearer who wants comfort and beautiful appearance that can boost their confidence while going out.